BIBLIOMETRIC ANALYSIS OF MORATORIUM - Nur Ain Nazihah Muhammad Rizal,; Hasyeilla Abd Mutalib,; Afiffudin Mohammed Noor, (Journal of Islamic, Social, Economics and Development, 2022)
This article presents a bibliometric analysis on moratorium which have been analyzed using the VOS viewer 1.6.18 to evaluate the global research trends, specifically the publication growth, publication outputs by countries, topics of interest, and co-occurrences of author keywords. Approximately 247 articles published between 1976 to 2022 were retrieved from the Scopus database. The findings have shown a growing trend in terms of publication outputs. Most of the publications were by the researchers from United States followed by United Kingdom and Canada. The keyword ‘moratorium’ has the highest occurrence in the publications followed by ‘United States’. A closer look at the co-occurrences of author keywords revealed that ‘moratorium’ has 7 links. It can be concluded that the results from the analysis could be used by future researchers to explore under research areas related to workplace moratorium.